Exploring Halal Awareness and Its Effects on Brand Image, Consumer Attitudes, and Purchase Decisions: A Study of Mixue in Malang - Mohammad Iqbal; Anni Rahimah; Sheyba Adinda Azigita (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Understanding the impact of Halal awareness on consumer behavior is crucial in markets with high sensitivity to Halal standards, as it can significantly influence brand perception and purchasing decisions. Despite the increasing importance of Halal certification, there is limited research on how Halal awareness specifically affects brand image, consumer attitudes, and purchase decisions in the context of the Indonesian market. This study aims to explore these relationships for Mixue in Malang. Utilizing an explanatory research design and quantitative methods, data were collected from a sample of 175 respondents through a non-probability sampling technique, specifically purposive sampling. Data analysis was conducted using descriptive techniques to interpret the relationships among the variables. The study finds a strong brand image positively impacts consumer attitudes toward the brand and encourages purchasing behavior. However, Halal awareness does not significantly affect consumer attitudes toward the brand or brand image directly. These insights underscore the complex interplay between Halal awareness, brand perception, and consumer behavior, highlighting the need for brands to enhance both Halal principles promotion and overall brand image to effectively drive consumer attitudes and purchase decisions.